Gagal Jatung Kongestif Pada Primigravida Hamil 31 Minggu Dengan Penyakit Jantung Bawaan: Sebuah Laporan Kasus - Nurmayeni; Zulfadli, Zulfadli (Medula, 2024)
Congenital Heart Disease (CHD) is a congenital heart disease where this disease has been present since a person was born. In pregnancy there are significant physiological changes in the cardiovascular system. These hemodynamic changes pose problems for mothers with congenital heart disease. This study is a case report. Data was obtained from a 31 year old woman who came with complaints of preterm pregnancy with complaints of severe shortness of breath since 2 weeks before entering the hospital with CHD. On physical examination, it was found that the general condition was seriously ill, compost mentis, blood pressure 107/84 mmHg, pulse 130x/minute, respiration 39x/minute, temperature 36.6°C, SpO2 70% NRM 15 lpm. On chest examination, a continuous murmur and wet rhonchi were found. Hematological examination showed an increase in ESR, urea, creatinine, SGOT and SGPT. Chest X-ray showed suspicion of pulmonary edema, bronchopneumonia and cardiomegaly. The results of the echocardiography examination showed PDA balanced shunt, PH, Severe TR, Moderate PR, Mild MR, RV mass 0.5 x 0.9 cm susp Infective Endocarditis. The patient was diagnosed with G1P0A0 26 weeks pregnant, not yet in labor with Dyspenu ec CHF with Congenital Heart Disease (PDA), Intrauterine JTH. Management of this patient is observation of general condition and vital signs, IVFD RL 500 cc 20 tpm, injection of furosemide 2 ampoules, ISDN 3 x 5 mg. Then transferred to the intensive care unit (ICU) and then terminated the pregnancy abdominally. The patient was declared dead on the 2nd day of treatment due to cardiogenic shock.